2016
DOI: 10.18203/2320-1770.ijrcog20151606
|View full text |Cite
|
Sign up to set email alerts
|

Role of echocardiography for assessment of cardiovascular haemodynamics during pregnancy

Abstract: Background: Pregnancy is associated with volume overload producing significant vascular and hemodynamic adaptations in cardiovascular physiology. Present study was designed to follow up gradual adaptations in cardiovascular hemodynamics during the course of pregnancy using Doppler echocardiography which is reproducible and noninvasive technique. Methods: In present prospective study of 50 women, were divided into 2 groups of 25 each: control group & study group (pregnant patient in I trimester, II trimester & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Other major cardiovascular changes associated with a normal pregnancy include increased stroke volume, cardiac output, heart rate, and venous return, as well as a paradoxical fall in systemic vascular resistance and blood pressure. 14 These hemodynamic alterations are mandatory to protect the mother from the consequences of hemorrhage and for the optimal growth of the fetus. 4 The other alteration in the maternal cardiopulmonary system is the effect of pregnancy on pulmonary artery pressure and left ventricular end-diastolic pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other major cardiovascular changes associated with a normal pregnancy include increased stroke volume, cardiac output, heart rate, and venous return, as well as a paradoxical fall in systemic vascular resistance and blood pressure. 14 These hemodynamic alterations are mandatory to protect the mother from the consequences of hemorrhage and for the optimal growth of the fetus. 4 The other alteration in the maternal cardiopulmonary system is the effect of pregnancy on pulmonary artery pressure and left ventricular end-diastolic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, speckle-tracking echocardiography and evaluation of ventricular strain, particularly GLS and GCS, have provided more comprehensive information regarding ventricular dysfunction in pregnant women with dyspnea and subclinical abnormalities. 14 …”
Section: Discussionmentioning
confidence: 99%
“…The calculated sample size was 323 by taking 70% prevalence. 15 Inclusion Criteria: Consecutive pregnant females irrespective of trimester were included in the study.…”
Section: Sample Sizementioning
confidence: 99%
“…15 Increased CO during the last trimester has not been projected sufficiently as a variety of studies are available showing a decrease, no change, or an increase, and have been mostly attributed to subjective adaptations of the mother during pregnancy along with interference by anthropometric variables of the mother and positioning of the body. 13,[16][17][18][19][20][21][22][23][24][25][26] Studies have also shown that this increased CO is likely to be enhanced in subsequent pregnancies. 27 The changes in CO are attributed to either neurohumoral factors such as estrogen and progesterone or placental factors.…”
Section: Cardiovascular Physiology Of the Heart Cardiac Output Duringmentioning
confidence: 99%